CONTRIBUTION OF RUSSIAN INTELLECTUALS AND THE RUSSIAN ADMINISTRATION TO THE PROCESS OF CULTURAL AND PUBLIC-POLITICAL DEVELOPMENT OF THE NORTH CAUCASUS IN THE XVIII - FIRST HALF OF XIX CENTRIES - Kidirniazov, Danial Sajdahmedovic (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers the role of Russian poets, writers , scientists and doctors in the process of cultural and political development of the region. The author notes that in order to speed up the process of training specialists among the representatives of the local ethnic groups the Russian authorities opened schools in the region, sent the elite children to central higher educational institutions of the country, established special “Caucasian” scholarships to support the young people who studied and were expected to be enlighteners and extensionists of Russian culture among the peoples of the North Caucasus.
Keywords: Dagestan; Russia; Caucasus; intellectuals; educational institutions; painters; national culture; enlighteners.